Comparative study of clinical indication-based DRLs with anatomical region-based DRLs in adult patients CT-scans in Yaounde - Cameroon. - MOIFO Boniface,; MOULION TAPOUH Jean Roger,; FOSSO Calliclès Stell,; TEINGUENG OUOGUE Francisse Xavier,; MBEDE Maggy,; DONGMO FOMEKONG Sylviane,; NEOSSI GUENA Mathurin, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Background : CT-scan is the major source of population exposure in diagnostic x-rays radiology. DRLs is one of the main optimization tools, initially established by anatomical region. CT examination protocols are adapted to the region of interest and to the indication. Therefore, DRLs by anatomical region may not be well appropriate for optimization. Objective : To compare clinical indication-based DRLs (CIB-DRLS) to anatomical region-based DRLs (ARB-DRLS) in adult patients CT-scans for better doses optimization. Methods: From January to July 2020, we carried out a cross-sectional dose-survey. CT dose metrics of patients undergoing head, chest, lumbar spine, abdomino-pelvic, and thoraco-abdomino-pelvic (TAP) CT examinations were collected prospectively in four highly attended health facilities in Yaounde. Thirteen most frequent clinical indications were retained (4 for head, 3 for chest, 3 for abdomino-pelvic, 2 for lumbar spine and one for thoraco-abdomino-pelvic) for a total of 697 scans. The sampling was consecutive and not exhaustive. The DRLs [75th percentile of Dose Length Product (DLP)] were assessed for each main clinical indication in a given anatomical region. DRL for each giving anatomical region (ARB-DRLS) were compare to DRLs based on clinical indication (CIB-DRLS) on that same region. This study was approved by the Institutional Ethical Review Board of the FMBS. Results: Of the 697 CT-examinations (55.4% men), the brain, chest, thoraco-abdomino-pelvic, abdomino-pelvic and lumbar spine CT-examinations represented respectively 38.2%, 25.5%, 11.0%, 10.6% and 14.7%. The ARB-DRLS (mGy.cm) was 1806.1 for head, 853.2 for chest, 3038.7 for abdomino-pelvic, 3050.5 for thoraco-abdomino-pelvic and 844.7 for lumbar spine CT-scans. CIB-DRLs were 11.6% and 7.1% higher than ARB-DRLs for intracranial space occupying lesion and chronic headache; it was 30.7% and 47.3% lower for head trauma and stroke. CIB-DRLs were 84.0% and 73.7% higher for pulmonary embolism and lung tumor; and 22.4% lower for covid-19 pneumonia than chest DRL. On the abdomino-pelvic region, it was 30.9% and 8.1% higher for pelvic tumor and hepatic mass ; and 34.9% lower for renal stones. For thoraco-abdomino-pelvic and lumbar spine CT-scans, CIB-DRLS were comparable to ARB-DRLs (difference of 0.9% to 5.0%). Conclusion: Clinical indication-based DRLs are more adapted for optimization than anatomical region-based DRLs because of large dose variations between different indications for the same anatomic region. Immediate actions should be taken for optimization of CT-pulmonary angiogram. Suggestion of national clinical indication-based DRLs is relevant. RÉSUMÉ  Contexte : Le scanner est la principale source d'irradiation de la population en radiodiagnostic. Les NRD initialement établis par région anatomique, constituent l'un des principaux outils d'optimisation. En pratique, les protocoles d'examen scanner sont adaptés à la région d'intérêt et à l'indication. Par conséquent, les NRD par région anatomique pourraient ne pas être adaptés à l'optimisation. Objectif : Comparer les NRD basés sur l'indication clinique (CIB-DRLs) aux NRD basés sur la région anatomique (ARB-DRLs) sur les scanners de patients adultes afin d'optimiser les doses. Méthodes : De janvier à juillet 2020, nous avons réalisé une étude transversale d’enquête dosimétrique. Les mesures de dose TDM des patients ayant des examens TDM de la tête, du thorax, du rachis lombaire, abdomino-pelvien et thoraco-abdomino-pelvien (TAP) ont été collectées prospectivement dans quatre structures sanitaires très fréquentées de Yaoundé. Treize indications cliniques les plus fréquentes ont été retenues (4 pour la tête, 3 pour le thorax, 3 pour l'abdomino-pelvien, 2 pour le rachis lombaire et un pour le thoraco-abdomino-pelvien) pour un total de 697 scanners. L'échantillonnage était consécutif et non exhaustif. Les NRD [75e percentile du produit dose-longueur (DLP)] ont été évalués pour chaque indication clinique principale dans une région anatomique donnée. Les NRD pour chaque région anatomique donnée (ARB-DRLs) ont été comparés aux NRD basés sur l'indication clinique (CIB-DRLs) sur cette même région. Cette étude a été approuvée par le comité d’éthique institutionnel de la FMBS. Résultats : Sur les 697 examens TDM (55,4 % d'hommes), les examens TDM du cerveau, du thorax, des thoraco-abdomino-pelviens, abdomino-pelviens et du rachis lombaire représentaient respectivement 38,2 %, 25,5 %, 11,0 %, 10,6 % et 14,7 %. L'ARB-DRLs (mGy.cm) était de 1806,1 pour les scanners de la tête, 853,2 pour les scanners du thorax, 3038,7 pour les scanners abdomino-pelviens, 3050,5 pour les scanners thoraco-abdomino-pelviens et 844,7 pour les scanners du rachis lombaire. Les CIB-DRLs étaient respectivement 11,6 % et 7,1 % plus élevés que les ARB-DRLs pour les processus expansifs intracrâniens et les céphalées chroniques ; ils étaient respectivement 30,7 % et 47,3 % plus bas pour les traumatismes crâniens et les accidents vasculaires cérébraux. Les CIB-DRLs étaient respectivement 84,0 % et 73,7 % plus élevés pour l'embolie pulmonaire et la tumeur pulmonaire, et 22,4 % plus faibles pour la pneumonie liée à la COVID-19 que pour les NRD thoraciques. Au niveau abdomino-pelvien, ils étaient respectivement 30,9 % et 8,1 % plus élevés pour la tumeur pelvienne et la masse hépatique, et 34,9 % plus faibles pour les calculs rénaux. Pour les scanners thoraco-abdomino-pelviens et lombaires, les CIB-DRLS étaient comparables aux ARB-DRLs (différence de 0,9 % à 5,0 %). Conclusion : Les NRD basés sur l'indication clinique sont plus adaptés à l'optimisation que les NRD basés sur la région anatomique, en raison des variations importantes de dose entre les différentes indications pour une même région anatomique. Des mesures immédiates doivent être prises pour optimiser l'angiographie pulmonaire par tomodensitométrie. Il est pertinent de proposer des NRD nationaux basés sur l'indication clinique.